PENGARUH BIAYA INTERNAL TERHADAP TINGKAT KELULUSAN MAHASISWA JURUSAN AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS MEDAN AREA MEDAN - Inda Yuni Arditha; Rosmaini Rosmaini (Universitas Medan Area, 2016)
The purpose of this study was to determine the extent of the internal cost of education in the Department of the Faculty of Economics, University Medan Area affect student graduation rates. To obtain the data and information needed, the authors used data collection methods as follows: Techniques of collecting data from this study are: Interviews, namely the question and answer directly ung with the parties involved in materials research the Faculty of Economics, University Medan Area and alumni , Data Analysis Techniques will be performed, the author will make a model of analysis that will be conducted by the author in order to answer the problem. To prove the hypothesis proposed in this study using multiple regression statistical tools. Thus 1.971> 1.28, the regression results received for not occur auto correlation in this study model. Standard Error (SE) obtained a value of 2.00262 means 20.02%. SE <R Square, away from Item No. 3 is known that the value of R Square of 27.8% means that 11.29% <89.9%, which means that the model is considered good. where t count 3.281> 1.697 t table which means that the hypothesis (Ho) received There is a positive influence internal charges against the graduation rate in Student Accounting Department of Economics, University Medan Area is true.